Common Error in Using English Tenses by EFL Students - Nurma Dhona Handayani (IdeBahasa, 2019)
Most of English foreign language learners (EFL) in the beginning level face some problems in learning English. They commited different kinds of errors and mistakes in learning English as a foreign language which were due to poor knowledge with grammar. Most of students considered that grammar was difficult, thus their motivation to learn English was also poor. Moreover, problems in foreign language learning especially in English were unavoidable. Therefore, the aim of this study was to identify common error in using English tenses by EFL students in the first semester at Putera Batam University. The instrument used was a test on basic English tenses and the data consisted of 50 students. The data sources were taken from the result of students’ test itself. It showed that students’ errors were categorized into six types; (1) Subject – auxiliary agreement, (2) Pronoun mistake or subject was wrong, meanwhile auxiliary verb or verb was right, (3) Auxiliary verb was correct meanwhile verb still added –es/s, (4) Auxiliary verb was wrong in sentence, (5) Double subject in sentence, (6) The sentence did not have subject or verb. Based on the result, it can be concluded some mistakes that students made were caused of they did not really understand the pattern of English tenses. Therefore, students should be given more attention and motivation to learn kinds of tenses correctly.